2011
DOI: 10.1007/s11095-011-0611-6
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Silicon (PSi) for Sustained Peptide Delivery: Effect of PSi Microparticle Surface Chemistry on Peptide YY3-36 Release

Abstract: PSi represents a promising sustained and tailorable release system for PYY3-36.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 45 publications
1
69
0
Order By: Relevance
“…PSi differs from many of the commonly used drug carriers since the loading of peptides is much easier compared with, for example, typically used polymer materials, and there is no need to use conditions that can be harmful for peptides such as strong solvents or high temperatures. Our research group demonstrated the promising features of PSi for sustained delivery of peptides (Kilpeläinen et al, 2009;Kovalainen et al, 2012;Huotari et al, 2013). In the following sections, we give an overview on the PSi material and its use in peptide delivery where the subcutaneous route has shown to be the preferable administration route.…”
Section: Porous Silicon As a Novel Materials For Peptide Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…PSi differs from many of the commonly used drug carriers since the loading of peptides is much easier compared with, for example, typically used polymer materials, and there is no need to use conditions that can be harmful for peptides such as strong solvents or high temperatures. Our research group demonstrated the promising features of PSi for sustained delivery of peptides (Kilpeläinen et al, 2009;Kovalainen et al, 2012;Huotari et al, 2013). In the following sections, we give an overview on the PSi material and its use in peptide delivery where the subcutaneous route has shown to be the preferable administration route.…”
Section: Porous Silicon As a Novel Materials For Peptide Deliverymentioning
confidence: 99%
“…4). Kovalainen et al (2012) studied the loading efficiency of PYY 3-36 in PSi with three different surface chemistries (Fig. 5).…”
Section: B Porous Silicon As a Peptide Delivery Systemmentioning
confidence: 99%
“…In 2007, Prestidge et al showed that a protein can be loaded and released from PSi (Prestidge et al 2007), and in 2009, Kilpel€ ainen et al showed in vivo that the loaded peptide was pharmacologically active after the loading (Kilpelainen et al 2009). In the following years, more results about subcutaneous administration of different peptides were published (Kilpelainen et al 2011;Kovalainen et al 2012Kovalainen et al , 2013. In addition to the remaining pharmacological activity, some other important findings were published recently.…”
Section: Subcutaneous Deliverymentioning
confidence: 99%
“…Since the first report revealing porous silicon particles-induced enhancement of paracellular delivery of insulin [25], sufficient advancement in developing pSi-based effective drug delivery systems for various kinds of therapeutic agents (e.g., pharmaceutical drugs (indomethacin (IMC) [26,27], doxorubicin (DOX) [28][29][30][31][32], paclitaxel [33], mitoxantrone dihydrochloride (MTX) [34,35], camptothecin (CPT) [36][37][38][39], and emodin [40]), therapeutic proteins (insulin [25,41], bovine serum albumin (BSA) [41], peptide [26,[42][43][44][45][46] ), and genes (siRNA [33,[47][48][49][50]), etc.) has been achieved in recent decades.…”
Section: Drug Deliverymentioning
confidence: 99%